Diabetes mellitus and nursing care for patients with chronic wounds (Research, Society and Development, 2022)
Introduction: The article aims to show the importance of diabetic foot care, and the primary role of the nurse trained to intervene in the midst of the complications that this disease has brought to thousands of people around the world. Objective: It aims to guide on the damage that diabetes can cause and warn about the necessary care, theoretically discuss this disease, alert patients with a diagnosis of diabetes who have ulcers, show the risks that can affect a patient with Diabetes, address about nursing care according to the state of your injury. Methodology: This is an integrative literature review, with a descriptive and qualitative interpretation, the following steps were taken: choice of the topic to be discussed, delimitation of the topic, search in databases, evaluation, data interpretation and a summary of the which was understood, after delimiting the subjects addressed according to the theme, articles were selected that refer to Diabetes Mellitus and patient care. Results: The problems caused by DM, in addition to affecting the physical state of the patient, can affect the social, cultural, and psychological conditions, patients with injury in many cases are shaken by their condition, and even fear of complications that can worsen your status. Conclusion: It is perceptible how important the role of the nurse directly with the patient is, whether in the part of changing dressings or performing treatments, in the evaluation of the feet and programming of self-care activities.